Análise de crescimento, trocas gasosas, potencila antioxidante e óleo essencial de Origanum vulgare L. ssp. vulgare - Carboni, Thaís Ribeiro [UNESP] (2013)
Origanum vulgare L. ssp. vulgare plants were grown in a Paddy-Fan greenhouse, with 100% (complete), 75%, 50%, and 25% Hoagland and Arnon (1950) #2 nutrient solution. The objective of the study was to evaluate the influence of the complete nutrient solution with the various diluted solutions, with regards to the growth of the Origanum vulgare L. ssp. vulgare, its gas exchange, antioxidant potential, and chemical composition during its growth. At 20, 40, 60, 80 and 100 days after transplanting the seedlings to the nutrient solution the following observations were measured: dry matter of leaves (DML) and total (DMT), and leaf area of the leaves (AL). These measurements were used to evaluate the physiological index, leaf area ratio (LAR), leaf weight ratio (LWR), net assimilation rate (NAR), and relative growth rate (RGR). The exchange of gases was evaluated at 20, 45 and 85 days after transplantation. At 20, 40, 60, 80 and 100 days after transplantation, fresh samples of foliage were collected and frozen in liquid nitrogen. These samples were stored in a freezer for later analyzes of pigmentation, total flavonoids, total phenols, ascorbic acid, and antioxidant potential. The essential oil was evaluated at 60, 80 and 100 days after transplantation. The experiment was randomized with the following factors: four repetitions in a design 4x5 (4 treatments and 5 harvest timeframe) to evaluate the growth and biochemical results, 4x3 for exchange of gases and 3X3 for the analysis of essential oil composition. The results of this experiment indicates that the variation of the nutrient solution’s concentration can stimulate or inhibit the growth Origanum vulgare L. ssp. vulgare, particularly in more concentrated solutions. Plants grown with more concentrated solutions showed a decrease of DML, DMT and AL, which interfered with the physiological indices. Additionally, a reduction in the exchange of gases was present, as well as an increase in the ...